Terpenes Functionalization: A Comparative Study in Catalytic Activity of Mesoporous Materials Modified with Ti and V - L. Canepa, Analia; E. Aguirre, Luis; R. Herrero, Eduardo; A. Eimer, Griselda; G. Casuscelli, Sandra (Current Catalysis, 2014)
The catalytic performance of mesoporous materials with a MCM-41 structure in the reaction of α-pinene oxidation with H2O2 was investigated by a comparative study of Ti-MCM-41and V-MCM-41 catalysts. These materials were prepared by hydrothermal synthesis, from theoretical molar ratios silicon / metal (Si/M) = 20, 60 and 240 in the initial synthesis gel. The results of the catalytic evaluation showed that for a similar molar content of metal in the materials (0.023 mole of metal/100 g of catalyst), Ti-MCM-41 presented the best TON values. Moreover, V-MCM-41 showed a lower efficiency of H2O2 than Ti-MCM-41, which can be attributed to the presence of clusters species (V-O-V)n and nanooxides VxOy which accelerate the decomposition reaction of peroxide to water. On the other hand, it is noteworthy that the polymerization degree of the surface vanadium species and the appearance of VxOy crystallites have a significant effect on the selectivity to the products obtained.
Keywords: Oxidation